Examining the impact of Legal Arizona Worker Act on native female labor supply in the United States - Christian Gunadi (IZA Journal of Labor Policy, 2020)
Low-skilled immigration has been argued to lower the price of services that are close substitutes for household production, reducing barriers for women to enter the labor market. Therefore, policies that reduce the number of low-skilled immigrants who work predominantly in low-skilled service occupations may have an unintended consequence of lowering women's participation in the labor market. This article examines the labor supply impact of the Legal Arizona Workers Act (LAWA), which led to a large decline in the low-skilled immigrant workforce of the state. The analysis shows no evidence that LAWA statistically significantly affected US-born women's labor supply in Arizona. This finding is partly explained by an increase in native workers in household service occupations due to LAWA, which offset the decline in immigrants in these occupations and caused the cost of household services to be relatively uninfluenced by the passage of LAWA.
Keywords: J21; J22; J61; 330; immigration; female labor supply; LAWA